Aspirin, platelet inhibition and cancer prevention. (17th November 2018) - Patrignani, Paola; Patrono, Carlo
Abstract: Several lines of evidence are consistent with the hypothesis that activated platelets contribute to colorectal tumorigenesis and metastatization through direct cell–cell interactions and the release of different lipid and protein mediators, and microvesicles. This review examines the clinical pharmacology of low-dose aspirin as a basis for discussing the mechanisms underlying the contribution of platelets to neoplastic transformation and progression of cancer via the development of metastases.